Telaah Waris dalam Bentuk Pemikiran Maqashid Syariah Jasser Auda - Andriyani, Gina (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstracts: This article examines the reconstruction of Islamic inheritance law through Jasser Auda's Maqāṣid al-Syarī‘ah approach, which emphasizes six system features: cognitive nature, wholeness, openness, interrelated hierarchy, multidimensionality, and purpose. This approach offers a more dynamic, contextual, and adaptive legal framework in responding to modern social changes, particularly on issues such as substitute heirs, gender justice, and orphan protection. This study uses a qualitative-descriptive method based on library research with content analysis of contemporary maqāṣid literature and reputable journals. The results show that Auda's approach allows for a fairer and more relevant reconstruction of inheritance law through systemic ijtihad, but still faces theological, methodological, and social challenges. This study recommends strengthening collective ijtihad, expanding the concept of obligatory wills, and formulating inheritance guidelines based on maqāṣid in the context of national law. These findings provide an important contribution to the development of contemporary inheritance law that is responsive and oriented towards public welfare.Keywords: Waris, Jasser Auda, System. Abstrak : Artikel ini mengkaji rekonstruksi hukum waris Islam melalui pendekatan Maqāṣid al-Syarī‘ah Jasser Auda yang menekankan enam fitur sistem: cognitive nature, wholeness, openness, interrelated-hierarchy, multidimensionality, dan purposefulness. Pendekatan ini menawarkan kerangka hukum yang lebih dinamis, kontekstual, dan adaptif terhadap perubahan sosial modern, terutama pada isu-isu seperti ahli waris pengganti, keadilan gender, dan perlindungan anak yatim. Penelitian ini menggunakan metode kualitatif-deskriptif berbasis studi pustaka dengan analisis isi terhadap literatur maqāṣid kontemporer dan jurnal bereputasi. Hasil penelitian menunjukkan bahwa pendekatan Auda memungkinkan rekonstruksi hukum waris yang lebih adil dan relevan melalui ijtihad sistemik, namun tetap menghadapi tantangan teologis, metodologis, dan sosial. Studi ini merekomendasikan penguatan ijtihad kolektif, perluasan konsep wasiat wajibah, serta penyusunan pedoman waris berbasis maqāṣid dalam konteks hukum nasional. Temuan ini memberikan kontribusi penting terhadap pengembangan fikih waris kontemporer yang responsif dan berorientasi kemaslahatan.Kata kunci: Waris, Jasser Auda, Sistem.